2020
DOI: 10.1080/08927022.2020.1810685
|View full text |Cite
|
Sign up to set email alerts
|

Finite-size effects of diffusion coefficients computed from molecular dynamics: a review of what we have learned so far

Abstract: The number of molecules used in a typical Molecular Dynamics (MD) simulations is orders of magnitude lower than in the thermodynamic limit. It is therefore essential to correct diffusivities computed from Molecular Dynamics simulations for finite-size effects. We present a comprehensive review on finitesize effects of diffusion coefficients by considering self-, Maxwell-Stefan, and Fick diffusion coefficients in pure liquids, as well as binary, ternary, and quaternary mixtures. All finite-size corrections, bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(92 citation statements)
references
References 172 publications
(283 reference statements)
1
91
0
Order By: Relevance
“…Figure 7 a displays that the thermal conductivities of GS-Hs as a function of the system size with a positive correlation. In fact, the relationship should be positive and gradually smooth towards a customization [ 42 ]. According to the corollary of Section 2.3 , Figure 7 b could be produced with simple operations.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 7 a displays that the thermal conductivities of GS-Hs as a function of the system size with a positive correlation. In fact, the relationship should be positive and gradually smooth towards a customization [ 42 ]. According to the corollary of Section 2.3 , Figure 7 b could be produced with simple operations.…”
Section: Resultsmentioning
confidence: 99%
“…Given that, the self-diffusion coefficient was affected by the system size, the obtained self-diffusion coefficient of DES species from MD simulations (Eq. 4 ) was corrected using the Yeh-Hummer correction, 48 51 , where and are the self-diffusion coefficients for the infinite (thermodynamics limit) and finite-size system, respectively. Also, η, T, and L are viscosity, temperature, constant Boltzmann, and length of the simulation box, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, it has been demonstrated that the YH correction term is not always adequate 69 . A review on this topic was recently published by Celebi et al 70 .…”
Section: Methodsmentioning
confidence: 99%